Roland Scriptoris ou de Lisbonne: un médecin, un professeur et un clerc portugais au XVe siècle - Mário Farelo (Medievalista)
This article aims at the biographical study of a Portuguese physician of the fifteenth century, still insufficiently known by the Portuguese historiography. Based on known and unpublished facts, it proposes a perspective into his public life, shared between the University, the service of the Great and the ecclesiastical environment, thus constituting a case of institutional and geographical mobility of a physician at the end of the Middle Ages.